Mechanical and Thermal Properties of UHPC Exposed to High-Temperature Thermal Cycling - In-Hwan Yang; Jihun Park (Advances in Materials Science and Engineering)
The effects of high-temperature thermal cycling (temperatures up to 500°C) and steel fiber contents on the mechanical and thermal properties of ultrahigh-performance concrete (UHPC) containing polypropylene (PP) fibers were investigated in this study. The different maximum temperatures for thermal cycling included 300, 400, and 500°C. The mechanical properties, including the compressive strength and tensile strength, and thermal properties, including the unit weight and thermal conductivity, of the UHPC specimens were measured. The experimental results indicated that the compressive strength, tensile strength, unit weight, and thermal conductivity decreased as the temperature increased to 500°C. Test results showed that for each maximum temperature, the reduction of the thermal conductivities from one to six thermal cycles was not significant. The thermal conductivity of the UHPC decreased as the unit weight of the UHPC decreased, and the thermal conductivity also decreased as the compressive strength of the UHPC decreased. Scanning electron microscopy (SEM) analysis showed that the microstructures of the UHPC specimens exposed to high temperatures contained voids due to the PP fiber melting. The porosity of the UHPC specimens increased as the maximum temperature of the thermal cycles increased, which decreased the unit weights and thermal conductivities of the UHPC specimens. Moreover, the porosity at a temperature of 500°C increased by 60.0, 74.5, and 123.4% for steel fiber contents of 1.0, 1.5, and 2.0%, respectively. It might be due to incompatible thermal expansion between the concrete matrix and steel fiber.